2017
DOI: 10.1186/s12920-017-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and characterization of breast cancer transcriptomes identifies large numbers of novel fusion-gene transcripts of potential functional significance

Abstract: BackgroundGene-fusion or chimeric transcripts have been implicated in the onset and progression of a variety of cancers. Massively parallel RNA sequencing (RNA-Seq) of the cellular transcriptome is a promising approach for the identification of chimeric transcripts of potential functional significance. We report here the development and use of an integrated computational pipeline for the de novo assembly and characterization of chimeric transcripts in 55 primary breast cancer and normal tissue samples.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…For both of these genes, this individual also showed sOutlier signal (median SPOT P = 0.0005 for EML6 and 0.0035 for SPTBN1). The identification of fusion transcripts has been of particular interest in cancer diagnosis and prognosis (27)(28)(29)(30), and both EML genes and SPTBN1 have been previously implicated in cancer-associated fusions (31,32).…”
Section: Rvs Can Affect Multiple Genes and Lead To New Gene Fusionmentioning
confidence: 99%
“…For both of these genes, this individual also showed sOutlier signal (median SPOT P = 0.0005 for EML6 and 0.0035 for SPTBN1). The identification of fusion transcripts has been of particular interest in cancer diagnosis and prognosis (27)(28)(29)(30), and both EML genes and SPTBN1 have been previously implicated in cancer-associated fusions (31,32).…”
Section: Rvs Can Affect Multiple Genes and Lead To New Gene Fusionmentioning
confidence: 99%
“…RNA-seq is a useful tool for genome-wide surveillance of gene fusions with nucleotide-level resolution of fusion junctions (22). Studies have demonstrated the potential to identify gene fusions via improved bioinformatics workflows (23)(24)(25), and therefore, RNA-seq can be used not only to identify driver gene fusions but also to detect novel and rare gene fusions in clinical laboratories. Gene mutations are usually analyzed via DNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Read mapping algorithms used for the analysis of clinically important samples use local de novo assembly to correct mapping errors and reference mismatches 10 . De novo assembly is currently used in transcriptome and cancer analysis, as gene fusions and genome rearrangements are common causes of malignant tumours 11 . Decreasing the costs of sequencing makes whole-genome sequencing an irreplaceable part of personalized medicine and cancer treatment.…”
Section: Introductionmentioning
confidence: 99%